The State and the Development of Industrial Plantation Forest - Sudarmalik Sudarmalik; Hariadi Kartodihardjo; Sudarsono Soedomo; Soeryo Adiwibowo (Jurnal Manajemen Hutan Tropika, 2014)
Development of industrial plantation forest is a form of principal-agent relationship, in which the Ministry of Forestry as a principal gives utilization permit to the entrepreneur as an agent, known as the Forest Timber Product Exploitation Permit on Planted Forest. This utilization permit obtained by the agents is operationally conducted by other parties through a cooperative agreement. The purpose of this study is to obtain an information regarding to the state position in the development of industrial plantation forest. The study was conducted in Riau Province, using the constructivist paradigm with phenomenological method. Data were obtained through in-depth interviews to selected informants. Data were also obtained from the review of documents to complement the interview. Data analysis was conducted using property rights and principal agent theories. The phenomenon of multi-chain transfer of the management rights of plantation forest that occoured in the observed companies showed that the state was unable to effectively control to the forest plantation. The study recommends that state should issue regulation to decrease or stops further transfer of the management rights of plantation forest. However, further study needs to overcome the existing over accumulation of plantation forest in a few hands.